Standardized Metadata Elements to Identify Access and License Information - Neylon, Cameron; Pentz, E.; Tananbaum, G. (2014)
The guide HowOpenIsIt? from SPARC, PLOS, and OASPA depicts a continuum of openness that varies by the rights accorded to readers, reuse rights, copyrights, author posting rights, automatic posting, and machine readability. Clearly, as the Guide points out, "not all Open Access is created equal." Currently, there is no standard metadata in use that succinctly defines these various levels of openness and licensing. In January 2013, NISO Voting Members approved a new work item proposal to develop a Recommended Practice on Open Access Metadata and Indicators (later re-named Access and Licensing Indicators) to address this gap. The goal of the project was to identify a standardized set of metadata elements to describe both the accessibility of a specific article and the available reuse rights.